Advances in Swarm Intelligence Third International Conference, ICSI 2012, Shenzhen, China, June 17-20, 2012 Proceedings, Part I - Tan, Ying.; Shi, Yuhui; Ji, Zhen.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book and its companion volume, LNCS vols. 7331 and 7332, constitute the proceedings of the Third International Conference on Swarm Intelligence, ICSI 2012, held in Shenzhen, China in June 2012. The 145 revised full papers presented were carefully reviewed and selected from 247 submissions. The papers are organized in 27 cohesive sections covering all major topics of swarm intelligence research and developments.
Keywords: Computer science; Computer Communication Networks; Computer software; Data mining; Artificial intelligence; Computer Science; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Computation by Abstract Devices; Computer Communication Networks; Data Mining and Knowledge Discovery